Diagnosing norms and norm change in rural Bangladesh: an exploration of gendered social norms and women’s empowerment - Chandramohan, Shivani; Salinger, Allison P.; Wendt, Amanda; Waid, Jillian; Kalam, Md. Abul; Delea, Maryann G.; Comeau, Dawn L.; Sobhan, Shafinaz; Gabrysch, Sabine; Sinharoy, Sheela (BMC public health, 2023)
Background: Gender-transformative public health programs often aim to address power inequities between men and women and promote women’s empowerment. However, to achieve transformative change, it is necessary to first identify the underlying norms that perpetuate these power imbalances. The objective of our study was to use Bicchieri’s theory of social norms and model of norm change to identify gendered norms and evidence of norm change amongst participants of the Food and Agricultural Approaches to Reducing Malnutrition (FAARM) trial in rural Sylhet Division, Bangladesh. Methods: We conducted ten life history interviews, 16 key informant interviews, and four focus group discussions with women and men in communities within the FAARM study site in rural, north-eastern Bangladesh. We performed a thematic analysis as well as a relational analysis of the data. Results: We found that social norms dictated the extent and ways in which women participated in household decisions, the locations they could visit, and their autonomy to use household resources. We also found evidence of changes to gendered social norms over time and the desire amongst some men and women to abandon restrictive norms. Certain intersecting factors, such as education and employment, were identified as facilitators and barriers to women’s empowerment and the related gendered expectations. Conclusions: Our findings corroborate existing norms literature, which highlights the strong role social norms play in influencing women’s empowerment and behaviour. Our study provides an example of rigorous qualitative methodology that others may follow to assess gendered social norms that can be targeted for transformative change.
Gesehen am 25.06.2024